Progression of the COVID-19 pandemic, Brazilian healthcare workers’ emotional burden and the effects on professional fulfillment at the end of the third wave: a longitudinal study - Loureiro, Sonia Regina; Zuardi, Antônio Waldo; Silveira, Isabella Lara Machado; Crippa, José Alexandre de Souza; Hallak, Jaime Eduardo Cecílio; Osório, Flávia de Lima (Frontiers in Psychiatry, 2023)
Introduction Even though the long-term effects of the COVID-19 pandemic on healthcare workers’ mental health remain unknown, such effects might negatively impact health services and patient safety, especially in countries like Brazil, where there is little investment in public health policies. Objectives To assess how the mental health indicators of Brazilian healthcare workers progressed between the beginning and 2 years after the pandemic (at the end of the third wave when there was a significant decrease in the number of new cases and deaths). Methods The sample comprised healthcare workers whose mental health indicators have been monitored since the beginning of the pandemic in Brazil. The potential participants were addressed via social media and contacted through class councils and health institutions across Brazil. A total of 165 participants answered instruments at the baseline and 2 years after the pandemic. Data were collected online using the Redcap platform and addressed symptoms of anxiety, depression, post-traumatic stress, insomnia, and burnout (emotional exhaustion, depersonalization, and professional fulfillment). Results Brazilian healthcare workers faced three periods of intensified incidence of new cases and deaths due to COVID-19 for 2 years. Approximately one-third of the sample still experiences high levels of anxiety, depression, and post-traumatic stress. Insomnia indicators remained the most prevalent compared to the baseline assessment, while post-traumatic stress symptoms (p = 0.04) and professional fulfillment (p = 0.005) decreased. Conclusion The lack of positive changes in mental health indicators coupled with decreased professional fulfillment over time highlights the pandemic’s chronic effects and the need for organizations to monitor these workers’ mental health, especially in developing countries like Brazil, where there is a high demand for health services and public policies are poorly structured and unstable.